Muslim Diaspora in the West: Negotiating Gender, Home, and Belonging By Haideh Moghissi and Halleh Ghorashi, eds. (Farnham, UK: Ashgate Publishing Ltd., 2011. 228 pages.) (American Journal of Islam and Society, 2013)
This excellent edited collection unpicks and disputes multifarious and intricateprocesses that underpin the homogenization, otherization, and vilification ofimmigrants from Muslim-majority countries, Muslim citizens, and individualswith a Muslim cultural background in the group of countries known as “theWest.” It does so through presenting a selection of essays that offer an insightinto the localized, day-to-day realities of people whose lives are currently definedby their link to Islam. The focus on gender, home, and belonging emphasizesthe particular challenge faced by Muslim women: Their bodies arethe battleground for the ideological wars fought by western governments onthe one hand, and by political Islamists on the other (pp. 30-31).At the same time, media outlets and governmental policies portray andessentialize all Muslims as a single, uniform community defined exclusivelyby their Muslimness, thereby ignoring any of their differences based on “nationalorigin, rural-urban roots, class, gender, language, lifestyle and degreeof religiosity, as well as political and moral conviction” (p. 2). As all of theessays demonstrate, these concerns about representation remain valid, despitethe critiques of historical and contemporary orientalism published by EdwardSaid over thirty years ago notwithstanding: Orientalism (1979) and CoveringIslam: How the Media and the Experts Determine How We See the Rest ofthe World (1981).The collection is a result of two conferences held in Toronto (2006) andAmsterdam (2008) to discuss these issues. It is organized around four themes:discourse, organizations, and policy; sexuality and family; youth; and spaceand belonging. The first theme is represented by different perspectives fromthe Netherlands, the United States, and the United Kingdom. Halleh Ghorashianalyzes the disempowering effects of supposedly “empowering courses” forimmigrant women of Muslim backgrounds and indicates how women themselvescritique the terms on which such courses are delivered. Fauzia ErfanAhmed writes about the deteriorating situation for female American Muslimcommunity leaders who are forced into silence despite a long history of femaleleadership since the time of slavery. Cassandra Balchin’s chapter focuses onMuslim women’s refusal to cede the discourse of their legal rights to both thegovernments and to patriarchal males within Muslim communities, who are ...